Cambridge IELTS 9 Student's Book with Answers: Authentic Examination Papers from Cambridge ESOL (IELTS Practice Tests) - Cambridge ESOL (Cambridge University Press, 2013)
Cambridge IELTS 9 contains four authentic IELTS past papers from Cambridge ESOL, providing excellent exam practice. The Student's Book with answers allows students to familiarise themselves with IELTS and to practise examination techniques using authentic test material. It contains four complete tests for Academic candidates, plus extra Reading and Writing modules for General Training candidates. An introduction to these different modules is included in each book, together with with an explanation of the scoring system used by Cambridge ESOL. A comprehensive section of answers and tapescripts makes the material ideal for students working partly or entirely on their own. Audio CDs containing the listening tests material are available separately, or as part of a self-study pack.